Ladies errant : wayward women and social order in early modern Italy - Shemek, Deanna (Book collections on Project MUSE., 1998)
The issue of a woman's place--and the possibility that she might stray from it--was one of early modern Italy's most persistent social concerns. Ladies Errant takes as its starting point the vast literature of this era devoted to the proper conduct and education of women. Deanna Shemek uses this foundation to present the problem of wayward feminine behavior as it was perceived to threaten male identity and social order in the artistic and intellectual articulations of the Italian Renaissance.Seeing errancy as an act of resistance rather than of error, Shemek carries her study beyond the didactic and prescriptive literature on femininity in early modern Italy to an arena in which theories about femininity are considered jointly with real and fictional instances of women's waywardness. As prostitutes, warriors, lovers, and poets, the women of Shemek's study are found in canonical texts, marginal works, and popular artistic activity, appearing, for instance, in literature, paintings, legal proceedings, and accounts of public festivals. By juxtaposing these varied places of errancy--from Ariosto's chivalric Orlando furioso to the prostitutes' race in the Palio di San Giorgio--Shemek points to the important contact between elite and popular cultures in early modernity, revealing the strength and flexibility of a gender boundary fundamental to early modern conceptions of social order.